Theological Functions for Human Life in the Perspective of Asian Theologies in the Era of Society 5.0 - GP Harianto (Millah: Journal of Religious Studies, 2022)
Human civilization has changed so quickly since humans entered the era of the industrial revolution. In this context, the role of theology seems to be dead, i.e. it has not yet functioned for the benefit of humanity in the world. This study examines the development of the meaning of theology, theology for Asian theologians, and the function of theology towards human suffering in the midst of world crises. This study used literature studies. The study's findings include the functions of Muangthai's Waterbuffalo Theology, Catholicism's Polulorum Progression, Choan-Seng Song, Indonesian Pluralism Theology, Secularism Theology, Liberation Theology, Indian Dalif Theology, Korean Minjung Theology, and Philippine Struggle Theology. Basic conclusion from the process of human understanding of God's will for the present and future of humans based on the Bible Humans use the formulation of theology to free themselves from the problems of life, including poverty, education, the economy, security, and politics. Man invites God to intervene in human life to depends on the goodness of God. Sound theology is rooted in God as a way of life that has a closer relationship with God, the Creator. This hope positions theology as a solution to human problems in the world, specifically giving humans life in holiness, giving humans life in eschatological victory, giving humans life as the Salt and Light of the World, and theology of safeguarding humanity's hope against suffering calamity.